Analysis of the effect of methadone and temperature on the development rate of Calliphora vicina (Diptera: Calliphoridae): A forensically important fly - Dawoud Kshvary; Yavar Rassi; Kourosh azizi; MOHAMMAD ALI OSHAGHI; SAYENA RAFIZADEH; ALI MOHAMMAD ALIMOHAMMADI; MARZIEA SHAHRIARI NAMADI; SEYEDEH ZAHRA PARKHIDEH (Smujo International, 2020)
Abstract. Keshavarzi D, Rassi Y, Azizi K, Oshaghi MA, Rafizadeh S, Alimohammadi AM, Namadi MS, Parkhideh SZ. 2020. Analysis of the effect of methadone and temperature on the development rate of Calliphora vicina (Diptera: Calliphoridae): A forensically important fly. Nusantara Bioscience 12: 87-91.  The development rate/time of flies is a scientific method to estimate the minimum time elapsed after death. Several studies have shown that opioids and temperature affect maggot growth rates. However, there are few published data that investigate the effect of ante-mortem methadone use on larval length of Calliphora vicina (Robineau-Desvoidy). Therefore, the purpose of this research was to investigate the effect of methadone and temperature on the development rate/time of this species. During this study, four rabbits were administered 0.10, 0.50, 1.0, and 10 mg/kg of methadone via gavage over a period of 14 days, and a five rabbit, which did not receive methadone, was used as a control. The rabbits' tissues were separated and exposed to maggots for rearing. Minimum developmental times of C. vicina life stages at six constant temperature regimes were provided. From hours 48 to 96, larvae feeding on tissues containing 10 mg/kg methadone developed more rapidly than those feeding on tissues containing 0.1, 0.50, and 1 mg/kg and also from the control. In the present study, development rate of C. vicina was linearly related to temperature (R2 = 0.96, p =0.02) between 16 and 32°C. The results revealed that the differences observed in the rates of development were sufficient to alter postmortem interval estimates based on larval development by up to 24 h.